Incidence of atrial fibrillation and thromboembolism in a randomised trial of atrial versus dual chamber pacing in 177 patients with sick sinus syndrome. Issue 6 (14th May 2004) - Kristensen, L; Nielsen, J C; Mortensen, P T; Pedersen, O L; Pedersen, A K; Andersen, H R
Abstract : Objective: To analyse the occurrence of atrial fibrillation (AF) and thromboembolism in a randomised comparison of rate adaptive single chamber atrial pacing (AAIR) and dual chamber pacing (DDDR) in patients with sick sinus syndrome and normal atrioventricular (AV) conduction, in which left atrial dilatation and decreased left ventricular fractional shortening had been observed in the DDDR group. Methods: 177 consecutive patients with sick sinus syndrome (mean (SD) age 74 (9) years, 104 women) were randomly assigned to treatment with one of three pacemakers: AAIR (n = 54), DDDR with a short rate adaptive AV delay (n = 60) (DDDR-s); or DDDR with a fixed long AV delay (n = 63) (DDDR-l). Analysis was intention to treat. Results: Mean follow up was 2.9 (1.1) years. AF at one or more ambulatory visits was significantly less common in the AAIR group (4 (7.4%) v 14 (23.3%) in the DDDR-s group v 11 (17.5%) in the DDDR-l group; p = 0.03, log rank test). The risk of developing AF in the AAIR group compared with the DDDR-s group was significantly decreased after adjustment for brady-tachy syndrome in a Cox regression analysis (relative risk 0.27, 95% confidence interval (CI) 0.09 to 0.83, p = 0.02). The benefit of AAIR was highest among patients with brady-tachy syndrome. Brady-tachy syndrome and a thromboembolic event before pacemaker implantation were independent predictors of thromboembolism during follow up (relative risk 7.5, 95% CI 1.6 to 36.2, p = 0.01, and relative risk 4.7, 95% CI 1.2 to 17.9, p = 0.02, respectively). Conclusions: During a mean follow up of 2.9 years AAIR was associated with significantly less AF. The beneficial effect of AAIR was still significant after adjustment for brady-tachy syndrome. Brady-tachy syndrome was associated with an increased risk of thromboembolism.